Niveles de fertilización nitrogenadas en el valor nutricional y la producción de gas in vitro en Erythrina poeppigiana - Álava Macías, Kevin Lenin (2022)
In Ecuador, the bovine livestock sector is one of the most important in agricultural production. In terms of production value, beef is second only to bananas and cocoa among food products. The objective of this research was nitrogen fertilization in nutritional value and in vitro gas production in Erythrina poeppigiana. A completely randomized design (DCA) was used for all 3variables, with 4 treatments (T0; 0 Kg N; T1; 100 Kg N; T2; 200 Kg N and T3; 300 Kg N) with 4 repetitions. The comparison of means using Tukey's test. Except for the in vitro ruminal degradation kinetics of Dry Matter (DM), Organic Matter (MO), Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and in vitro gas production. Bromatological composition analyzes of dry matter (DM), organic matter (MO), neutral detergent fiber (NDF) and acid detergent fiber (ADF) were performed. The in vitro digestibility of dry matter (DIVMS), organic matter (DIVMO), neutral detergent fiber (DIVFDN) and acid detergent fiber (DIVFDA), the technique of Tilley and Terry (1963)